A inibição da enzima δ-aminolevulinato desidratase por monossacarídeos não é mediada pela oxidação de grupos -sh - Gabriel, Diogo (2004)
Heme pathway enzyme δ-aminolevulinate dehydratase (δ-ALA-D) is a good marker for oxidative stress and metal intoxication. This sulfhydrylic enzyme is inhibited in several oxidative pathologies like lead, mercury and aluminum intoxication, selenium organic species exposition and diabetes. Oxidative stress is one of cause of diabetes complications. This occurs due non-enzymatic glucose-mediated reaction, which can change structure of proteins and impair enzymes function. In our study, influences of high glucose, fructose and ribose concentrations on δ-ALA-D activity were evaluated in vitro. The possible mechanism, which underlies δ-ALA-D inhibition, was investigated using lysine, DTT, and t-butylamine. Reducing sugars (glucose, fructose and ribose) inhibit δ-ALA-D and inhibition order was fructose>ribose=glucose. Enzyme inhibition did not involve oxidation of its critical sulfhydryl groups because DTT and sodium borohydride did not modify enzyme inhibition. Furthermore, medium TBARS were not modified by exposition to monosaccharide. Authors diverge to mechanism inhibition of δ-ALA-D by glucose. Either glycosilation or oxidative stress are implicated in model of enzyme impairment. We concluded that δ-ALA-D inhibition caused by high concentrations of reducing sugar is mediated by enzyme glycosilation that lead to conformational changes, which can impair enzyme catalytic function.